Rural territorial dynamics in Latin America - Chiriboga, Manuel (2013)
This article draws from the preliminary findings of an ongoing appliedresearch program on rural territorial dynamics carried out by the Latin American Center for Rural Development (RIMISP). The article provides some initial findings on 4 territories, of the 11 territories that are part of the overall study. The case studies include the island of Chiloé in southern Chile, the province of Tungurahua in Ecuador, a dairy farm region of Santo Tomás Nicaragua and Cuatro Lagunas near Cuzco Perú. Rural areas in Latin America are characterized by their dual nature with agro-exporting enclaves linked to global value chains alongside impoverished peasant economies, leading to differentiated policy recommendations. The research attempts to find relationships between reduced poverty and inequality in winning regions, measured by three variables, with issues of access to resources, human capital, political empowerment, markets and institutions, with particular attention to innovative social coalitions.